Household formation over time: Evidence from two cohorts of young adults - Daniel Cooper; María José Luengo-Prado (Federal Reserve Bank of Boston, 2016)
This paper analyzes household formation in the United States using data from two cohorts of the national Longitudinal Survey of Youth (NLSY) - the 1979 cohort and the 1997 cohort. The analysis focuses on how various demographic and economic factors impact household formation both within cohorts and over time across cohorts. The results show that there are substantial differences over time in the share of young adults living with their parents. Differences in housing costs and business-cycle conditions can explain up to 70 percent of the difference in household-formation rates across cohorts. Shifting attitudes toward co-habitation with parents also play a role.
Keywords: J11; D10; R20; 330